Diagnosis and Numerical Simulation of Low-level Wind Shear over the Hengduan Mountains in Winter - Ren Juzhang; Yang Xue; Tao Yun; Fu Zhijia; Chen Yan; Zhong Yahan; Wang Man; Jin Yan (应用气象学报)
Cangyuan Washan Airport, located at Delong Mountain in the Hengduan Mountains, is prone to low level wind shear during takeoff and landing in winter, which is of great harm to aviation safety, and aviation departments attach great importance to it. It is also a key problem in refined weather forecasting and early warning under complex terrain. Therefore, it is essential to examine changes in low-level wind circulation around the airport. Using NCEP/NCAR reanalysis data, airport weather station data, encrypted automatic weather station data and wind profile radar data, a low-level wind shear turn-around event at Cangyuan Wushan Airport on 29 December 2021, is diagnosed and analyzed by statistical and numerical simulation methods. Results indicate that during winter, the southwest airflow prevails in the Hengduan Mountains, and the surface wind speed is relatively low. The small-scale local valley wind circulation in the east of Cangyuan Washan Airport is obvious. During daytime, the prevailing valley wind blows from the valley toward the airport. At night, the mountain wind blows from the airport back to the valley. Additionally, a vertical downdraft predominates in the approach area. However, there is a consistent southwest breeze in the afternoon. When the wind speed increases to more than 5.0 m·s-1, the prevailing southwest wind will cross the mountain, and the cross-mountain air on the ground will converge with the increased valley wind in the approach area, resulting in instantaneous vertical upward movement and forming low-level wind shear. The rapid fluctuations in wind direction and speed near the ground in the dam area on the east side of the airport significantly affects aviation safety. With the weakening of the solar radiation, the prevailing wind and valley wind begins to weaken at night, and the mountain wind circulation shifts towards the dam area on the east side of the airport, resulting in an increase in vertical subsidence movements. Numerical simulation results confirm that under the action of solar radiation heating, the prevailing southwest air flow increases in the Hengduan Mountains during daytime, and passes over the Delong Mountain in the afternoon, making the surface wind of the airport into a consistent southwest wind. The surface wind speed of the airport exceeds 5.0 m·s-1, and it strengthens in the valley area on the east side of the airport under the action of the cross-mountain air flow. The convergence of valley winds and downslope flow leads to vertical updrafts, which increases the vertical instability of the lower atmosphere in the dam area on the east side of the airport. The phenomenon results in a downwind shear layer, which leads to aircraft turbulence.